SPIRITUAL AND MORAL PRINCIPLES OF STRENGTHENING HISTORICAL CONSCIOUSNESS IN THE EDUCATIONAL SYSTEM (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
This article describes the role of historical consciousness in raising the spiritual culture of young people, the importance of spiritual and moral principles of strengthening historical consciousness in the educational system.